Interactive Web Based Tests With Immediate Auto Feedback Via E Mail To The Instructor: Software And Illustration - Muyshondt, Arnoldo; Ing-Chang, Jong (Association for Engineering Education - Engineering Library Division Papers, 2001)
Web-based tests are increasingly utilized in education. This paper is written to contribute a basic yet versatile software, with illustration, for creating interactive web-based modules for tests with immediate auto-feedback to a specified e-mail address for the instructor. Each module assists students in learning new material by offering “tips,” without providing answers right away, when wrong answers are chosen by students. The software is segmented into five program files, where the first two are subject specific while the other three are general. Being independent of web sites, the three general program files need no changes by users. All software files are freely downloadable from a given web site. Beginning instructors can readily create web-based modules by directly modifying the two subject specific program files, which are included in the paper. I. Introduction The World Wide Web (WWW) is an environment where the information created is accessible on demand, anytime, and anywhere. It has been used by organizations and individuals for various purposes. In education, it is capable of allowing on-demand access to any information and mate- rial for a given course or for tutoring, which an instructor provides at a web site. In particular, the WWW can be used to great advantage in teaching high enrollment courses as well as distance education. Increasing efforts to create web-based educational material on the WWW clearly point 1-7 to the trend of using web publication as an alternative mode in modern education. This paper is an extension of a recent contribution by the authors. It presents a basic yet versatile software that uses Practical Extraction and Report Language (PERL) and Common Gateway In- 8-9 terface (CGI) scripting to manipulate data files to readily create modules for interactive on-line testing with immediate feedback. It allows as well as promotes learning because appropriate “tips” are offered, without providing answers right away, when wrong answers are chosen by students. Note that PERL is a programming language like C or FORTRAN. A CGI script is simply a program that is run on a web server based on input from a browser. It enables users to interact with the web pages. For example, when a web user fills in a form or a search dialog on the web, the user has used a CGI script. Generally, CGI scripts are basic sets of Proceedings of the 2001 American Society for Engineering Education Annual Conference & Exposition Copyright © 2001, American Society for Engineering Education